Inventarisasi dan Identifikasi Laba-laba pada Terong (Selanum melogena L.) di Kabupaten Ogan Ilir, Sumatera Selatan - Sulha, Niken Ayu; Fakhriyah Putri, Aisyah; Erfiari Palami, KMS Kahesa; Ariska, Meylia; Dona, Rama; Doni, Rama; Umayah, Abu; Gunawan, Bambang; Arsi, Arsi (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2022)
Sulha NA, Putri AF, Palami KE, Ariska M, Dona R, Doni E, Umayah A, Gunawan B, Arsi A. 2022. Inventory and identificarion of spider on eggplant (Selanum melogena L.) in Ogan Ilir Regency, South Sumatra. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 589-595. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Eggplant (Solanum melongena L.) was one of the most popular plants in Indonesia as a daily food ingredient. However, growth was often disrupted by insect pest attacks which caused economic losses. In this case, proper control was needed so that pests did not cause massive losses. One of the controls was using predatory insects. Spiders are predators that could control insect populations. This paper aimed to inventory and identify spiders on eggplant plants in Ogan Ilir Regency, South Sumatra, Indonesia. The sampling method was carried out by using the direct method by hand. The research was in the form of a field survey using the Purposive Random Sampling method. Sampling of spiders in the field was carried out 3 times in each field and in the morning. The results show that there are 5 species belonging to 2 families. The six species are Oxyopes javanus, Oxyopes matiensis (Oxiopidae), Larinioides sclopetarius, Lycosa pseudoannulata, Misumena vatia (Thomisidae). There is a species that is only found in one village, namely M. vatia. The dominant spider species found were O. javanus, O. matiensis, M. vatia and L. sclopetarius. Therefore, the number of species that have been found is 5 species of spiders from the order Coleoptera. The spiders found have the potential as natural enemies for insect pests.